The Identification Of Waroeng Special Sambal’s Resources And Capabilities In Achieving Sustainable Competitive Advantages - Amri, Ahmad Munadhir (Adpebi International Journal of Multidisciplinary Sciences, 2022)
This study aims to identify Waroeng SS’s resources and capabilities in achieving its sustainable competitive advantages, which are aimed to achieve sustainable competitive advantages.Primary and secondary data are used in this research. The primary data were obtained from interviews and questionnaires. While the secondary data were obtained from literatures relating to Waroeng SS and culinary industry, from both online and offline resources. This study uses value chain analysis of resources and company capabilities to analyze competitive advantages by assessing resources and capabilities (strategic importance and strategic relative strength, and VRIO Framework to analyze sustainable competitive advantages).Based on the analysis results using value chain analysis, 30 resources and capabilities in Waroeng SS are found. The results show that there are 21 resources and capabilities that can be used as competitive advantages. From the results of the analysis, three resources and capabilities can be used as sustainable competitive advantages for Waroeng SS. First, Waroeng SS management owns farming land for raw materials that and work together with farmers, second, R & D team that is specifically responsible for maintaining product quality to remain consistent and equal to each outlet, and third, they have the ability to screen and provide training programs according to what employee needs. Result of Waroeng SS’s resources and capabilities identification that can be made a sustainable competitive advantages, the company are expected to give more focus on it’s resources and capabilities. So, the company not only gain competitive advantages, it’s also achieve the sustainable competitive advantages.